Development of a solitary koinobiont hyperparasitoid in different instars of its primary and secondary hosts. (July 2016) - Harvey, Jeffrey A.; Fei, Minghui; Lammers, Mark; Kos, Martine; Zhu, Feng; Heinen, Robin; Poelman, Erik H.; Gols, Rieta
Graphical abstract: Highlights: Mesochorus gemellus is a solitary primary hyperparasitoid of Cotesia species. We compared development of M. gemellus in L3-L5 instars of Pieris brassicae . P. brassicae has been parasitized by Cotesia glomerata in the first instar. Approximately 40% of C. glomerata larvae were parasitized in L3-L5 P. brassicae . Development time but not adult body mass varied with host instar parasitized. Abstract: Parasitoid wasps are excellent organisms for studying the allocation of host resources to different fitness functions such as adult body mass and development time. Koinobiont parasitoids attack hosts that continue feeding and growing during parasitism, whereas idiobiont parasitoids attack non-growing host stages or paralyzed hosts. Many adult female koinobionts attack a broad range of host stages and are therefore faced with a different set of dynamic challenges compared with idiobionts, where host resources are largely static. Thus far studies on solitary koinobionts have been almost exclusively based on primary parasitoids, yet it is known that many of these are in turn attacked by both koinobiont and idiobiont hyperparasitoids. Here we compare parasitism and development of a primary koinobiont hyperparasitoid, Mesochorus gemellus (Hymenoptera: Ichneumonidae) in larvae of the gregarious primary koinobiont parasitoid, Cotesia glomerata (Hymenoptera: Braconidae) developing in the secondary herbivore host, Pieris brassicae (Lepidoptera: Pieridae). As far as we know this is the first study to examine development of a solitary primary hyperparasitoid in different stages of its secondary herbivore host. Pieris brassicae caterpillars were parasitized as L1 by C. glomerata and then these parasitized caterpillars were presented in separate cohorts to M. gemellus as L3, L4 or L5 instar P. brassicae . Different instars of the secondary hosts were used as proxies for different developmental stages of the primary host, C. glomerata . Larvae of C. glomerata in L5 P. brassicae were significantly longer than those in L3 and L4 caterpillars. Irrespective of secondary host instar, every parasitoid cluster was hyperparasitized by M. gemellus but all only produced male progeny. Male development time decreased with host stage attacked, whereas adult male body mass did not, which shows that M. gemellus is able to optimally exploit older host larvae in terms of adult size despite their decreasing mass during the pupal stage. Across a range of cocoon masses, hyperparasitoid adult male body mass was approximately 84% as large as primary parasitoids, revealing that M. gemellus is almost as efficient at exploiting host resources as secondary (pupal) hyperparasitoids.